Shareholder engagement on environmental, social, and governance performance - Barko, Tamas (Journal of business ethics, 2022)
We study behind-the-scenes investor activism promoting environmental, social, and governance (ESG) improvements by means of a proprietary dataset of a large international, socially responsible activist fund. We examine the activist’s target selection, forms of engagement, impact on ESG performance, drivers of success, and effects on the targets’ operations and value creation. Target firms are typically large and visible, perform well, and have high liquidity (stock turnover) and low ESG performance. Engagement induces ESG rating adjustments: firms with poor ex ante ESG ratings experience a ratings increase after complying with the activist’s demands, whereas firms with high ex ante ESG ratings experience a ratings decrease following the revelation of their ESG problems. Activism that is focused on environmental and social issues is more likely to succeed if targets are ESG-sensitive (i.e., they have a strong ex ante ESG profile). Successful engagements boost targets’ sales. Risk-adjusted excess stock returns (with four-factor adjustment and relative to a matched sample of non-engaged firms) of successful engagements outperform those of unsuccessful engagements by 2.7%. Results are especially strong for firms with low ex ante ESG scores. Specifically, targeted firms in the lowest ex ante ESG quartile outperform matched peers by 7.5% in the year after the end of the engagement. Our results thus suggest that the activism regarding corporate social responsibility generally improves ESG practices and corporate sales and is profitable to the activist. Taken together, we provide direct evidence that ethical investing and strong financial performance, both from the activist’s and the targeted firm’s perspective, can go hand-in-hand together.